اثر القيادة التحويلية على الابتكار التنظيمي - صحراوي ميمية (Universty Of El-oued جامعة الوادي, 2024)
الملخص: تهدف هذه الدراسة إلى قياس أبعاد القيادة التحويلية في الابتكار التنظيمي لدى الموظفين بجامعة الشهيد حمه لخضر بالوادي؛ حيث تمّ اختيار أبعاد القيادة التحويلية المتمثلة في التأثير المثالي، الاعتبار الفردي، الاستثارة الفكرية، الدافع الإلهامي، كما تم تقسيم الابتكار التنظيمي إلى بعدين هما: الابتكار التكنولوجي و الابتكار الإداري. ولتحقيق ذلك استُخْدمت الاستمارة كأداة لجمع البيانات، التي وزعت على 200 موظفا من الجامعة حيث تم استرجاع 144 استمارة قابلة للدراسة. وقد تمت معالجة هاته البيانات بواسطة برنامج التحليل الاحصائي الــــــــــSPSS - إصدار 25- والتحقق من الصدق و الثبات لخصائصها، كما أُجريَت اختبارات بواسطة المتوسطات الحسابية و الانحرافات المعيارية، تحليل التباين الأحادي والانحدار الخطي البسيط و المتعدد. وتوصّلت الدراسة إلى: ان درجة ممارسة الابتكار التنظيمي كانت متوسطة وأيضا وجود علاقة ارتباط معنوية بين المتغيّريْن. كما تبين ايضا وجود أثر ذو دلالة احصائية بين أبعاد القيادة التحويلية وأبعاد الابتكار التنظيمي عند مستوى دلالة 0.05، ومن خلال النتائج تبين وجود فروق ذات دلالة إحصائية لأثر أبعاد القيادة التحويلية في ممارسة أبعاد الابتكار التنظيمي تعزى للبيانات الشخصية ( الجنس، السن، المؤهل العلمي، الاقدمية). وتوصّلت الدراسة إلى جملة من الاقتراحات أهمها: وضع برامج تدريبية لإعداد قادة تحويلين وتنمية قدراتهم لممارسة مهامهم داخل المؤسسات الجامعية، وضرورة اهتمام المؤسسة أكثر بالابتكار التنظيمي لمواجهة التحديات ومواكبة التغيرات. Résumé : فرنسية أو انجلزية This study aimed to know the effect of transformational leadership on organizational innovation among employees at the University of Echahide Hama Lakhdar. The dimensions of transformational leadership represented in ideal influence, individual consideration, intellectual stimulation, and inspirational motivation were selected. Organizational innovation was divided into two dimensions: technological innovation and Administrative innovation. To achieve the objectives of the study, we used the questionnaire as a data collection tool, which was distributed to 200 employees of the university, where 144 study able forms were retrieved. standard, one-way analysis of variance, simple and multiple linear regression. Among the most important results reached: the existence of a statistically significant effect between transformational leadership and organizational innovation at the level of significance 0.05, and also the existence of a significant correlation between the dimensions of transformational leadership and organizational innovation, that the degree of practicing organizational innovation was medium, and through the results also it was found that there is Statistically significant differences with the impact of transformational leadership in the practice of organizational innovation due to personal data (gender, age, educational qualification, seniority) A number of suggestions were reached, the most important of which are: developing training programs to prepare transformational leaders and developing their capabilities to exercise their tasks within university institutions, the need for the institution's attention More organizational innovation to meet challenges and keep pace with changes.
دراسة حالة جامعة الشهيد حمه لخضر –الوادي-
أطروحة دكتوراه في العلوم الاقتصادية و التجارية و علوم التسيير
Keywords: القيادة التحويلية، الابتكار التنظيمي، التأثير المثالي، الاعتبار الفردي، الاستثارة الفكرة، الدافع الإلهامي.; Transformational leadership; organizational innovation; ideal influence; individual consideration; idea stimulation; inspirational motivation